(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article provides a scientific and theoretical in-depth analysis of the philosophical foundations of material, spiritual and economic life in the development of society and their interconnectedness. The dialectical unity of material production processes, the system of economic relations and spiritual values in the development of man and society is revealed. Also, the interaction of these factors in the development of modern society, their role in ensuring social stability and sustainable development is substantiated from a philosophical point of view.